2011
DOI: 10.1248/bpb.34.1448
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Soy Isoflavone Genistein on Ischemia-Reperfusion in the Rat Small Intestine

Abstract: Ischemia-reperfusion (I/R) injury of the intestine is an important factor associated with high rates of morbidity and mortality. Intestinal I/R is a common clinical problem in the settings of severe burns, circulatory shock and strangulation ileus. Intestinal I/R damages remote organs and promotes multi-organ failure. It has been shown that enteral feeding before ischemic insults is beneficial for reducing organ injury and improving survival after intestinal I/R. In that study, the authors used a standard comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Several bioactive compounds were discovered in Radix Astragali such as isoflavonoids, astragalosides and polysaccharides (Sun et al, 2010). Recent findings suggest that isoflavonoids can attenuated ischemic and reperfusion injury in animal model (Sato et al, 2011;Watanabe et al, 2007). Calycosin is the major isoflavonoids of Radix Astragali.…”
Section: Discussionmentioning
confidence: 99%
“…Several bioactive compounds were discovered in Radix Astragali such as isoflavonoids, astragalosides and polysaccharides (Sun et al, 2010). Recent findings suggest that isoflavonoids can attenuated ischemic and reperfusion injury in animal model (Sato et al, 2011;Watanabe et al, 2007). Calycosin is the major isoflavonoids of Radix Astragali.…”
Section: Discussionmentioning
confidence: 99%
“…The main components of soy isoflavones, including genistein, daidzein, glycitein and biochanin A [4,5], have been demonstrated to possess various biological properties and exert antiestrogenic [6], anticarcinogenic [7,8], antioxidant [9], anti-inflammatory [10,11] as well as immune-modulatory functions [12]. Increasing evidences have suggested that soy isoflavones may have beneficial effects in the prevention and treatment of inflammatory disorders [5,13] and diarrheal diseases [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that flavonoids may have genotoxic properties (Fox et al, 2012;Lehmann et al, 2005) and may act as pro-oxidants (Michels et al, 2005;van Zanden et al, 2003), or they may have significant protective effects against oxidative damage (Hagen et al, 2012;Sato et al, 2011;Widyarini et al, 2012;Yen & Lai, 2003).…”
Section: Introductionmentioning
confidence: 99%